Regional interdependencies and macroeconomic crises notes on Mercosur - Heymann, Daniel (ECLAC SantiagoCL, 2001)
Contains brief comments about the experience of Mercosur in macroeconomic matters, some reflections about the possibilities for concerted regional actions. Reviews aspects of the recent behaviour of the economies of the area (focusing on Argentina and Brazil). Comments on the characteristics of macroeconomic interdependencies, and analyzes circumstances that have conditioned macroeconomic coordination within the region. Considers some policy options for regional cooperation in crisis situations.